The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jpcc.8b11518
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Formation of Conductive Mesocrystalline Superlattices with Cubic PbS Nanocrystals at the Liquid/Air Interface

Abstract: We report the formation of conductive mesocrystalline superstructures of cubic PbS nanocrystals (NCs) through directional cross-linking with organic semiconductors at the liquid/air interface monitored simultaneously by in situ grazing incidence small angle X-ray scattering and grazing incidence X-ray diffraction. We determine the superlattice type, its symmetry and parameters, and the atomic orientation of NCs from the time-resolved scattering patterns. The superlattice contraction follows an exponential deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
0
22
0
2
Order By: Relevance
“…Structural investigation of self-assembled Au 32 -NC microcrystals. To verify the crystallinity of self-assembled microcrystals, grazing-incidence small-angle X-ray scattering (GISAXS) measurements are performed, which is a common technique to investigate the structural properties of nanoparticle assemblies in thin films or at interfaces [33][34][35] . The GISAXS pattern of an ensemble of hundreds of individual microcrystals with different azimuthal orientation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structural investigation of self-assembled Au 32 -NC microcrystals. To verify the crystallinity of self-assembled microcrystals, grazing-incidence small-angle X-ray scattering (GISAXS) measurements are performed, which is a common technique to investigate the structural properties of nanoparticle assemblies in thin films or at interfaces [33][34][35] . The GISAXS pattern of an ensemble of hundreds of individual microcrystals with different azimuthal orientation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[13] X-ray scattering found interparticle distances of precisely one molecular length, suggesting that the p-cloud of the phthalocyanine stacks is oriented perpendicular to the binding axis between two NCs. [200] It seems likely that this highly specialized scenario is not of a universal nature and that other binding motifs between NCs and molecular p-systems are possible (see section 3.2). However, to systematically exploit this and other structural diversities in hybrid nanostructures for triplet harvesting, a better understanding of an optimal binding geometry is needed.…”
Section: Fabrication Principles For Triplet Exciton Harvesting With Cmentioning
confidence: 99%
“…For metal phthalocyanines, optical spectroscopy has suggested that the molecular π‐system forms small stacks of H‐aggregates, which separate adjacent NCs [13] . X‐ray scattering found interparticle distances of precisely one molecular length, suggesting that the π‐cloud of the phthalocyanine stacks is oriented perpendicular to the binding axis between two NCs [200] . It seems likely that this highly specialized scenario is not of a universal nature and that other binding motifs between NCs and molecular π‐systems are possible (see section 3.2).…”
Section: Fabrication Strategies For Optoelectronic Applicationsmentioning
confidence: 99%
“…[ 22 ] This results in long‐range ordered and highly conductive SLs, since the rigid and relatively long ligands reduce the energy barrier for charge transport without deteriorating structural order, as it was shown previously. [ 23,24 ] Hence, the hybrid system of PbS NCs and Cu4APc is an ideal compromise between increased electronic coupling and long‐range ordered SLs, which was a fundamental prerequisite for this study. By means of soft‐lithographic microcontact printing, [ 25 ] we transfer stripes of PbS NC‐Cu4APc SLs with a width ( W ) of roughly 4 µm onto trenches of ≈1 µm length ( L ) between two gold contacts on X‐ray transparent Kapton and Si/SiO x substrates.…”
Section: Figurementioning
confidence: 99%